Development of recipes for poultry snacks and their quality assessment - I. V. Asfondyarova; A. A. Abutalimova; V. A. Demchenko (Новые технологии, 2025)
Introduction. Snacks are an important part of our diet and represent one of the fastest growing segments of the food industry. They can ensure the emergence of innovative meat snacks on the market; this fact opens up better opportunities for meat industry workers, consumers and specialists. The goal of the meat snacks industry is to improve the quality and stability of traditional meat snacks or to release new products with increased nutritional value, functional characteristics, more convenient packaging and improved sensory properties such as taste, aroma, consistency [1]. Meat snacks are produced from presalted meat of any kind, followed by drying or curing. They are produced in the form of sausages, whips, meat chips, jerky and pork ears, packed in vacuum packaging. Their cost varies from 60 to 394 rubles per 50 grams [2]. In St. Petersburg the consumer market is dominated by a range of snack products made from pork and beef with a large number of additives that are not always wholesome for a consumer. At the same time, snacks based on poultry meat are limited. The selection of natural ingredients will provide the human body with necessary biologically active substances. The goal of the research is to produce meat snacks and assess their quality. The Research objectives are to develop snack recipes and study their quality based on organoleptic and physicochemical parameters. The methods used are analysis, experiment, measurement. The Results. The organoleptic quality assessment of the snacks obtained during the experiment has been carried out on a 5-point scale; physical and chemical parameters have been studied using standard methods. Five snack recipes with different flavors have been developed from marinated poultry meat, then heat-treated for 5.5 hours. Conclusion. Having assessed the organoleptic and physicochemical properties, it has been found that the snack with the addition of turmeric has the best consumer organoleptic properties, receiving a final average score of 4.85. The moisture content in all the snack samples studied ranges from 37.2 to 46%. The mass fraction of salt does not exceed 1%.